Epidemiology and Survival of Patients With Brainstem Gliomas: A Population-Based Study Using the SEER Database - Liu, Huanbing; Qin, Xiaowei; Zhao, Liyan; Zhao, Gang; Wang, Yubo (Frontiers in Oncology, 2021)
BACKGROUND: Brainstem glioma is a primary glial tumor that arises from the midbrain, pons, and medulla. The objective of this study was to determine population-based estimates of the epidemiology, incidence, and outcome of brainstem gliomas. METHODS: The data of patients with brainstem gliomas diagnosed between 2004 and 2016 were extracted from the SEER database. Descriptive analyses were conducted to evaluate the distribution and tumor-related characteristics of patients with brainstem gliomas. The possible prognostic indicators were analyzed by Kaplan-Meier curves and a Cox proportional hazards model. RESULTS: The age-adjusted incidence rate was 0.311 cases per 100,000 person-years between 2004 and 2016. A total of 3387 cases of brainstem gliomas were included in our study. Most of the patients were white and diagnosed at 5-9 years old. The most common pathology type was ependymoma/anaplastic ependymoma. The median survival time was 24 months. Patients with tumors less than 3 cm in size had a better prognosis. Surgery was effective in improving overall survival. Radiotherapy and chemotherapy showed no evidence of improving overall survival. CONCLUSION: Brainstem gliomas can be diagnosed at any age. Ependymoma/anaplastic ependymoma is the most common pathological diagnosis. The prognosis is poor, and timely diagnosis and surgery are effective in improving the prognosis. We suggest that more attention should be paid to the treatment of patients with brainstem gliomas.